2018
DOI: 10.1186/s40545-018-0139-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of primary labeling of medicines manufactured by Nepalese pharmaceutical industries

Abstract: BackgroundAppropriate labeling of marketed medicines is necessary to fulfill the regulatory provisions and ensure patient medication safety. This study aimed to assess the primary labeling of medicines manufactured and marketed by Nepalese pharmaceutical industries.MethodsWe assessed the primary labeling of all medicines available at the pharmacy of Chitwan Medical College Teaching Hospital (CMCTH), Chitwan, Nepal, between November 2017 to December 2017. Medicines were assessed as required by Drug Standard Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Most of the 759 pharmaceutical products from 37 Nepali pharmaceutical companies inspected in Chitwan in 2017 missed at least one critical information on the label such as drug quantity, name of pharmacopoeia, serial number of pharmaceutical industries, price list, drug classification and information in Nepali language. 10 The reports showed that labels of 84% of drugs did not provide the directions for use. Similarly 90% of drug samples (n=40) in Kathmandu did not comply with the existing regulatory requirement on labelling and 42.5% brands did not indicate the pharmacopoeial standard.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the 759 pharmaceutical products from 37 Nepali pharmaceutical companies inspected in Chitwan in 2017 missed at least one critical information on the label such as drug quantity, name of pharmacopoeia, serial number of pharmaceutical industries, price list, drug classification and information in Nepali language. 10 The reports showed that labels of 84% of drugs did not provide the directions for use. Similarly 90% of drug samples (n=40) in Kathmandu did not comply with the existing regulatory requirement on labelling and 42.5% brands did not indicate the pharmacopoeial standard.…”
Section: Resultsmentioning
confidence: 99%
“…The DDA in Nepal is equivalent to the US Food and Drug Administration (FDA) and is responsible to prevent the misuse or abuse of drugs and allied pharmaceutical substances 8. Few studies in the past have indicated the circulation of substandard, counterfeit and unregistered drugs in the Nepali market 9–11. DDA Nepal recalls marketed drugs if the drugs do not fulfil any requirement as indicated in the Drug Act 2035 B.S 8.…”
Section: Introductionmentioning
confidence: 99%
“…Providing required information on the label is another issue. Majority of the pharmaceutical products inspected in Chitwan in 2017 involving 759 drugs from 37 Nepali pharmaceutical companies did not meet the regulatory standards of primary labeling 8 . Most of them missed at least one critical information on the label such as drug quantity, name of pharmacopoeia, serial number of pharmaceutical industries, price list, drug classification, and information in Nepali language.…”
Section: Resultsmentioning
confidence: 99%
“…The DDA also aims to prevent the misuse or abuse of drugs and allied pharmaceutical substances, the false or misleading information relating to the efficacy and use of drugs and, to control the production, sale, distribution, export, import, storage and consumption of those drugs which are not safe, efficacious, and of standard quality 6 . Few studies in past have indicated the circulation of substandard, counterfeit, and unregistered drugs in the Nepali market 7,8,9 . The DDA Nepal recalls marketed drugs if the drugs do not fulfill any requirement as indicated in the drug act 2035 B.S.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of proper labeling of medicines in minimizing medication errors are well known [1]. Falsified, misleading, unclear, insufficient, and ambiguous information given on labels is among the major defects reported to be associated with improper labeling practices [2][3][4][5]. Thus, enhancement of the consistency and the quality of medicine labels are sought through the regulatory frameworks.…”
Section: Introductionmentioning
confidence: 99%